PERCEPTION OF ATTITUDE OF HEALTH-CARE PROVIDERS, ACCESSIBILITY AND COST OF HEALTHCARE SERVICE ON CLIENT SATISFACTION OF CHILD HEALTHCARE SERVICES IN PHCS IN ALIMOSHO LGA OF LAGOS STATE. - Alausa, Waheed Moa-Liberty; Odunuga, Lateefat Tinuola (Practicum Psychologia, 2019)
The objectives of this study was to examine clients’ satisfaction with attitude of health-care service providers, accessibility, and cost of child health services in Primary Health-care Centres (PHCs) in Alimosho Local Government Area of Lagos State. Descriptive Cross-sectional survey design was adopted and a sample size of 222 women caregivers were randomly selected in stratified sampling of 6 among the 29 PHCs in Alimosho LGA. The age of the women ranges from 16 to 47, giving a mean age of 33 years, and their children were under-five years old. Three hypotheses were tested, and association between variables was found using Chi square. The results show that though clients were satisfied with attitude of the health-care providers (83.1%; χ2=1.933, P>.05), accessibility (84%; χ2=1.034, P>.05), and cost of child health-care service (83%; χ2=2.516, P>.05), there were no significant association between any of the variables and clients’ satisfaction. Based on findings of the study, recommendation was made that Government should continuously train health-care service providers on interpersonal skills to handle their various clients. PHCs should also be built closer to the community so that people can easily access the hospitals within a short distance to their homes.